Understanding financial fluctuations and their relation to macroeconomic stability - Nora Guarata; Carolina Pagliacci (Inter-American Development Bank (IDB), 2017)
This paper examines how financial fluctuations and macroeconomic stability interact in the case of Venezuela, acknowledging that financial conditions deteriorating the macroeconomic environment can arise with both good and bad macroeconomic performance. An empirical methodology is provided that constructs two indexes, which are fully interpretable and are constructed with a minimum set of assumptions applied to a large number of financial time series. Structural interpretation of indexes is pursued using a structural VAR (SVAR) that associates macroeconomic stability with financial indexes. For Venezuela, a deterioration of procyclical financial conditions relates to financial margin reductions and expansions in banks' balance sheets, which are mostly triggered by unexpected increases in net primary money creation. Such expansions tend to appear in situations of declining macroeconomic stability. Worse countercyclical financial conditions are instead associated with situations of rising bank profitability, deleveraging and increased banking instability. In this case, fragility tends to materialize in periods of ameliorated macroeconomic stability.
hdl:11319/8332
Keywords: E30; G10; E00; 330; Financial cycle; Financial conditions index; Macroeconomic stability